2007
DOI: 10.2519/jospt.2007.2416
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging Assessment of Abdominal Muscle Function During Drawing-in of the Abdominal Wall: An Intrarater Reliability Study

Abstract: A ssessment of function of the deep abdominal musculature in the laboratory has largely used methodologies such as functional movement tasks and fine-wire electromyography (EMG). 13,10,11,15,27 While fine-wire EMG is primarily restricted to laboratory research, rehabilitative ultrasound imaging (RUSI) offers a noninvasive and simpler method of assessing deep lumbopelvic muscle function. Recent work has shown that measures of transversus abdominis (TrA) muscle contraction, 20 internal oblique (IO) muscle contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
116
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 25 publications
14
116
0
11
Order By: Relevance
“…No significant increase of ICC was registered after introducing a third repeated measurement. These findings are consistent with previous studies [6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…No significant increase of ICC was registered after introducing a third repeated measurement. These findings are consistent with previous studies [6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 83%
“…These parameters are regarded quick and easy to obtain, non-invasive indicators of the TrA performance which is crucial for stability and control of the lumbar spine [2,3]. Authors conclude that US measurement of TrA thickness generally shows acceptable reliability in healthy persons [6][7][8][9][10][11][12][13][14][15][16] and patients with low back pain [12,[17][18][19][20][21][22]. Results concerning TrA thickness change are still contradictory or unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Across-day reliability may be of interest to physiotherapists who perform repeated assessments of abdominal muscle function over time, 16 and factors such as relocation of the original imaging site and reproduction of the same transducer pressure and orientation, as well as maintenance of these factors during muscle contraction, could adversely affect reliability. 16 The aims of the present study were to evaluate test-retest and intrarater reliability of 2-dimensional ultrasound imaging of the IRD at rest and during abdominal crunch and drawing-in exercises, and to verify the differences in IRD related to the postpartum condition.…”
Section: T T Resultsmentioning
confidence: 99%
“…Several studies have reported good reliability for measurement of individual abdominal muscle thicknesses at rest or in contracted state [10,11,18,30]. Also ultrasonic biofeedback is used to teach TrA contraction in patients with LBP [2,3,23].…”
Section: Introductionmentioning
confidence: 99%